2020
DOI: 10.37335/ijek.v8i2.98
|View full text |Cite
|
Sign up to set email alerts
|

Organisational Green Behavioural Change: The Role of Change Management

Abstract: The pervasive environmental crisis across the globe has been traced to unsustainable business practices of corporations. This live-threatening phenomenon continues to generate vivacious debates, with scholars and other green stakeholders suggesting certain behavioral patterns as a solution to the scourge.  However, while some organisations are realising the need for green processes and behaviors to key to sustainability practices, they are being confronted with the dilemma of the most effective ways to go abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 11 publications
1
19
0
Order By: Relevance
“…Larger social networks imply more representative and trustworthy sources of information, allowing farmers to take better decisions, chose their traders, get access to better contracting, improve their living conditions and earnings and increasing agricultural productivity (Nazari & Hasbullah, 2008). Information exchange in the other hand is positively influenced by horizontal relationship only in contracted production (Ik & Azeez, 2020). This supports previous evidence and suggests that in spot markets the interaction of farmers does not enable them to improve information exchange with buyers (Brito et al, 2015).…”
Section: The Role Of Access To Information In Tradingsupporting
confidence: 87%
“…Larger social networks imply more representative and trustworthy sources of information, allowing farmers to take better decisions, chose their traders, get access to better contracting, improve their living conditions and earnings and increasing agricultural productivity (Nazari & Hasbullah, 2008). Information exchange in the other hand is positively influenced by horizontal relationship only in contracted production (Ik & Azeez, 2020). This supports previous evidence and suggests that in spot markets the interaction of farmers does not enable them to improve information exchange with buyers (Brito et al, 2015).…”
Section: The Role Of Access To Information In Tradingsupporting
confidence: 87%
“…In this context, Lu et al (2012) argue that interpersonal trust implies a moderating effect on the trading relationship satisfaction. On the other hand, many authors claim that satisfaction may also be affected by changes in production process (e.g., Ik & Azeez, 2020). This relationship is supported by the idea that it creates more pressure and leads to more efforts from farmers.…”
Section: Relationship Qualitymentioning
confidence: 99%
“…These decisions are critically based on a significant number of factors from across the globe [127]. Servitisation literature follows a similar trend to that of I4.0 and CE.…”
Section: Linking Servitisation and Cementioning
confidence: 92%
“…Meanwhile, Chang et al [44] and Cainelli et al [139] suggested that a higher revenue stream is contingent on market share. Weking et al [14] also advocate that firms will capture a higher customer base that will translate into a higher rate of return when firms serve larger market [44,127]; by offering distinctive and customised products [83] along with value-added services [23,34,150] •…”
mentioning
confidence: 99%